2001
DOI: 10.2131/jts.26.337
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between toxicity and cadmium accumulation in rats given low amounts of cadmium chloride or cadmium-polluted rice for 22 months.

Abstract: To clarify toxic effects of long-term oral administration of low dose cadmium (Cd) on the liver and kidney, six groups of female Sprague-Dawley rats were fed a diet containing Cd-polluted rice or CdCl2 at concentrations up to 40 ppm, and killed after 12, 18, and 22 months. With toxicological parameters, including histopathology, there was no evidence of Cd-related hepato-renal toxicity, despite a slight decrease of mean corpuscular volume and mean corpuscular hemoglobin of red blood cells with 40 ppm CdCl2. Do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 34 publications
4
9
0
Order By: Relevance
“…It has also been proposed that cadmium exerts a direct toxic effect on the glomerulus [47] . Also, the present studies agree with Shibutani et al [45] , who reported that cadmium can affect on renal tubules damage and then glomerular filtration impairment. In the present investigations, administration of Camel's milk with cadmium chloride significantly decreases and brought the concentration of urea in the rat's serum to near normal levels.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It has also been proposed that cadmium exerts a direct toxic effect on the glomerulus [47] . Also, the present studies agree with Shibutani et al [45] , who reported that cadmium can affect on renal tubules damage and then glomerular filtration impairment. In the present investigations, administration of Camel's milk with cadmium chloride significantly decreases and brought the concentration of urea in the rat's serum to near normal levels.…”
Section: Discussionsupporting
confidence: 93%
“…As a result of cadmium activity, one notices renal tubule damage and then glomerular filtration impairment [45] . This may account for the increase of urea concentration in the animals receiving cadmium chloride.…”
Section: Discussionmentioning
confidence: 99%
“…20,21) The metallothionein concentration in the kidneys in the 5-, 20-, and 40-ppm groups increased at every time point in a dose-dependent manner. 15) In the liver, metallothionein increased in the 20-and 40-ppm groups from 12 months, but the liver Cu concentration did not increase. Pearson correlation coefficient analysis also revealed a clear relationship between Cd and Zn, but not between Cd and Cu.…”
Section: Discussionmentioning
confidence: 85%
“…15,16) The results showed that the retention rate of Cd did not change with the dosage or the treatment period and that renal toxicity was not induced by long-term oral administration of low amounts of Cd, in contrast to the effects of high-dose Cd administration, although tissue accumulation occurs.…”
Section: Introductionmentioning
confidence: 95%
“…Cd is an industrial and environmental pollutant arising primarily from battery, electroplating, pigment, plastics, fertilizer industries and cigarette smoking. The accumulation of Cd is consistently increased when a certain amount is ingested continuously (Shibutani et al, 2001). When Cd enters the body, it reaches the liver within the first 6h and binds to metallothionein, which is a protein with a low molecular weight (6000-10,000 Da) and rich in cystein (Haki Kara et al, 2005 andChan andCherian, 1993).…”
Section: Introductionmentioning
confidence: 99%